Megakaryocytes maintain homeostatic quiescence and promote post-injury regeneration of hematopoietic stem cells - Zhao, Meng; Perry, John M; Marshall, Heather; Venkatraman, Aparna; Qian, Pengxu; He, Xi C; Ahamed, Jasimuddin; Li, Linheng (Nature medicine, 2014)
Two papers in this issue, by Bruns et al . and Zhao et al ., show that megakaryocytes constitute a niche for hematopoietic stem cells in the mouse bone marrow and produce factors that regulate hematopoietic stem cell quiescence and proliferation. Multiple bone marrow stromal cell types have been identified as hematopoietic stem cell (HSC)-regulating niche cells 1 , 2 , 3 , 4 , 5 , 6 , 7 . However, whether HSC progeny can serve directly as HSC niche cells has not previously been shown. Here we report a dichotomous role of megakaryocytes (MKs) in both maintaining HSC quiescence during homeostasis and promoting HSC regeneration after chemotherapeutic stress. We show that MKs are physically associated with HSCs in the bone marrow of mice and that MK ablation led to activation of quiescent HSCs and increased HSC proliferation. RNA sequencing (RNA-seq) analysis revealed that transforming growth factor β1 (encoded by Tgfb1 ) is expressed at higher levels in MKs as compared to other stromal niche cells. MK ablation led to reduced levels of biologically active TGF-β1 protein in the bone marrow and nuclear-localized phosphorylated SMAD2/3 (pSMAD2/3) in HSCs, suggesting that MKs maintain HSC quiescence through TGF-β–SMAD signaling 8 , 9 . Indeed, TGF-β1 injection into mice in which MKs had been ablated restored HSC quiescence, and conditional deletion of Tgfb1 in MKs increased HSC activation and proliferation. These data demonstrate that TGF-β1 is a dominant signal emanating from MKs that maintains HSC quiescence. However, under conditions of chemotherapeutic challenge, MK ablation resulted in a severe defect in HSC expansion. In response to stress, fibroblast growth factor 1 (FGF1) signaling from MKs transiently dominates over TGF-β inhibitory signaling to stimulate HSC expansion 10 , 11 . Overall, these observations demonstrate that MKs serve as HSC-derived niche cells to dynamically regulate HSC function.